(untitled) (Research, Society and Development, 2021)
This study aimed to compare two hormonal protocols for fixed-time embryo transfer (FTET) in dairy cows based on the moment of PGF2α application. A total of 2,172 crossbred Bos indicus cows were used. According to the embryo recipient synchronization protocol, the cows were divided into two treatments: Conventional and MMSINCRO (test treatment). The Conventional protocol consisted of inserting a device containing progesterone and administering estradiol benzoate on Day 0. On Day 8, progesterone was removed and PGF2α, eCG and estradiol cypionate were applied. On Day 10, the animals received GnRH. FTET was performed on Day 17. The MMSINCRO protocol consisted of the insertion of progesterone and administration of estradiol benzoate on Day 0. On Day 7, animals received PGF2α. On Day 9, the progesterone was removed and the animals received eCG and estradiol cypionate. On Day 11, GnRH was applied. The FTET was performed on Day 18. The conception rate of the MMSINCRO treatment recipients (52%) was significantly higher than that of the Conventional protocol (33%). The qualitative evaluation of the corpus luteum showed a better quality in the MMSINCRO treatment. Thus, it was possible to conclude that for FTET in dairy cows, it is advisable to use the MMSINCRO protocol in the recipients, which was able to increase the conception rate. This finding provides an improvement in the reproductive efficiency of dairy cattle, and consequently, a greater production of milk and dairy products on dairy farms.